Particle swarm optimization based inverter impedance control to perform harmonic sharing in islanded microgrid - Muhammad, Lailatul Niza (2019)
Distributed generation (DG) is referred as an integration of different kinds of renewable energy sources used to generate electricity at or near the location where it will be utilized, such as solar panels, combined heat and power and others. Voltage source inverters located between the DG and utility grid plays an important part in injecting clean and reliable power into the grid. Several control issues arises from the grid integration of PV based system such as grid stability, power quality control, loads sharing and others. A power quality index known as total harmonics distortion (THD) is an indicator used to measure the harmonics content in a distorted waveform. The THD of voltage and current for grid connected system should be below 5% as mentioned in IEEE 519-2014 Standard. This project focuses on the power quality control of harmonics in grid current due to nonlinear load in the system. A comparative study between current control techniques namely Hysteresis current controller, Proportional-Integral(PI) controller and combination of Proportional-Integral (PI) with Hysteresis current controller is conducted to control the harmonics distortion in grid current. The impact of nonlinear load on grid current is analyzed by measuring the performance of THDi level in MATLABTM Simulink software environment.